(untitled) (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2012)
This article offers a reflection about the value and relevance of ethical banking in the actual economic context and outlines the pillars on which those initiatives are based. The approach is based on the consideration of the place that credit has in our societies, as the key factor to understand the social impact of the financial intermediation. The analysis focuses on the human rights perspective and leads todescribe the processes that ground the ethical banking initiatives that promote the right to credit, underlying its status as a tool for political action, as collective action networks committed to social transformation.